Islamic Education Perspective - Adi Kasman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Islamic studies is a learning material that is studied and studied by students of high Islamic colleges, is also one component of general courses that must be followed by all of them in all the faculties and all the majors, which also covered a wide range of Islamic sciences , both of which dealing with the law, education, history, thoughts in Islam, even studied about the different kinds of approach in understanding the religion, the source of the teachings, the characteristic teachings of Islam itself, and the methodology of understanding about Islam in a comprehensive manner with diversity theory combined with model or type of research. Such approaches include a "normative theological, anthropological, sociological, psychological, historical, cultural, and philosophical approaches"